Problem wyboru liczby klas w analizie klas ukrytych - Kasprzyk, Iwona (The Problem of Choosing the Number of Classes, 2009)
The latent class analysis is one of multivariate techniques of the contingency table which is based on discrete data. This method was introduced by Lazarsfeld [1968]. The main aim of this article is to show simulation research results. The results describe choosing the correct number of classes with respect to number of sample size, number of latent classes and number of variables. In this article, various criteria of choosing the correct model were used. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 291-298